IMPLEMENTATION OF ELECTRONIC TRIAL (E-LITIGATION) ON THE CIVIL CASES IN INDONESIA COURT AS A LEGAL RENEWAL OF CIVIL PROCEDURAL LAW - Kurniawan, M. Beni (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
Civil case trial based on HIR/RBg takes months or even more than a year, which sets a bad precedent for judicial institution because it tends to be complicated, and closed. A proverb voiced, â€œReporting the loss of goats instead of missing cows,â€ increasingly the publicâ€™s negative impression towards judicial institution. Responding to these conditions, the Supreme Court issued a Supreme Court Regulation (PERMA) No. 1 of 2019 concerning Case Administration and Court Trials Electronically. The research questions, how is the implementations of electronic trial (e-litigation) on civil cases in Indonesia judicial institutions? The research method used is literature study, in particular normative legal research, which is descriptive analytical. PERMA No 1 of 2019 has provided benefits for internal judiciary and justice seekers. Where case registration is done electronically without needing go to court. The payment of court fees is simply by transferring to a virtual account and the summons of parties are carried out electronically to an electronic domicile. It is not just limited to that the trial is also carried out electronically, from the first trial until the reading of the judgeâ€™s verdict. However, there are challenges for the successful of electronic litigation from the aspect of legal substance, the electronic trial regulated at PERMA rule out HIR/R.Bg whose hierarchy is above of that PERMA. In aspects of legal structure, It is needed the completed infrastructure and human resources. As well as aspects of legal culture, the enthusiasm of justice seekers who use e-court services.